Intersectionality-Based Policy Analysis of HIV-Related Stigma as a Structural Barrier to Health Equity: Evidence from Ghana with Implications for Sub-Saharan Africa - Atta-Doku, John Foster (International Journal of Health Concord, 2026)
Background: Despite substantial advances in HIV prevention and treatment, HIV-related stigma remains a persistent structural barrier to equitable healthcare, particularly in Sub-Saharan Africa (SSA), where the epidemic is most concentrated. Ghana exemplifies this challenge, as progressive HIV policies coexist with entrenched forms of stigma that disproportionately affect marginalized populations. This study applies the Intersectionality-Based Policy Analysis (IBPA) framework to examine how intersecting social identities and policy assumptions shape HIV-related stigma and influence access to health services. Methods: A conceptual policy analysis was conducted using the IBPA framework. The analysis synthesized evidence from peer-reviewed literature, national HIV policy documents, and institutional reports relevant to HIV stigma, health equity, and healthcare access in Ghana and the broader SSA context. The analytical process focused on four IBPA dimensions: power relations, intersecting categories, policy assumptions, and equity implications. Result: The analysis revealed that HIV-related stigma persists despite formal non-discrimination policies, reflecting enduring structural and institutional inequities. Marginalized populations, including young women, men who have sex with men, sex workers, and rural communities, experience compounded barriers arising from the intersection of gender, sexuality, socioeconomic status, and geographic location. Current HIV policies predominantly emphasize biomedical interventions while inadequately addressing the social and structural determinants of stigma. These policy blind spots contribute to inequitable healthcare access and reduce the effectiveness of HIV prevention, treatment, and care services. Conclusion: Applying the IBPA framework demonstrates that HIV-related stigma is fundamentally a structural and intersectional challenge that requires policy responses extending beyond biomedical approaches. Embedding intersectionality, equity, and community engagement into HIV policy and service delivery may strengthen stigma reduction, improve healthcare utilization and treatment adherence, and advance health equity in Ghana and across Sub-Saharan Africa.